Syntrophic Growth of Desulfovibrio alaskensis Requires Genes for H(2) and Formate Metabolism as Well as Those for Flagellum and Biofilm Formation - Krumholz, Lee R. (Appl Environ Microbiol, 2015)
In anaerobic environments, mutually beneficial metabolic interactions between microorganisms (syntrophy) are essential for oxidation of organic matter to carbon dioxide and methane. Syntrophic interactions typically involve a microorganism degrading an organic compound to primary fermentation by-products and sources of electrons (i.e., formate, hydrogen, or nanowires) and a partner producing methane or respiring the electrons via alternative electron accepting processes. Using a transposon gene mutant library of the sulfate-reducing Desulfovibrio alaskensis G20, we screened for mutants incapable of serving as the electron-accepting partner of the butyrate-oxidizing bacterium, Syntrophomonas wolfei. A total of 17 gene mutants of D. alaskensis were identified as incapable of serving as the electron-accepting partner. The genes identified predominantly fell into three categories: membrane surface assembly, flagellum-pilus synthesis, and energy metabolism. Among these genes required to serve as the electron-accepting partner, the glycosyltransferase, pilus assembly protein (tadC), and flagellar biosynthesis protein showed reduced biofilm formation, suggesting that each of these components is involved in cell-to-cell interactions. Energy metabolism genes encoded proteins primarily involved in H(2) uptake and electron cycling, including a rhodanese-containing complex that is phylogenetically conserved among sulfate-reducing Deltaproteobacteria. Utilizing an mRNA sequencing approach, analysis of transcript abundance in wild-type axenic and cocultures confirmed that genes identified as important for serving as the electron-accepting partner were more highly expressed under syntrophic conditions. The results imply that sulfate-reducing microorganisms require flagellar and outer membrane components to effectively couple to their syntrophic partners; furthermore, H(2) metabolism is essential for syntrophic growth of D. alaskensis G20.